PSD-95 expression controls l-DOPA dyskinesia through dopamine D1 receptor trafficking - Porras, Gregory (American Society for Clinical Investigation, 2012)

(untitled)
l-DOPA–induced dyskinesia (LID), a detrimental consequence of dopamine replacement therapy for Parkinson’s disease, is associated with an alteration in dopamine D1 receptor (D1R) and glutamate receptor interactions. We hypothesized that the synaptic scaffolding protein PSD-95 plays a pivotal role in this process, as it interacts with D1R, regulates its trafficking and function, and is overexpressed in LID. Here, we demonstrate in rat and macaque models that disrupting the interaction between D1R and PSD-95 in the striatum reduces LID development and severity. Single quantum dot imaging revealed that this benefit was achieved primarily by destabilizing D1R localization, via increased lateral diffusion followed by increased internalization and diminished surface expression. These findings indicate that altering D1R trafficking via synapse-associated scaffolding proteins may be useful in the treatment of dyskinesia in Parkinson’s patients.